Study on Bundung Grass (Scirpus grossus L.) as The Natural Fibre for Fishing Gear Material with the Breaking Strength and Elongation Test - Nehe Mia Sitohang; Nofrizal '; Irwandy Syofyan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was aimed to study about the potential of bundung grass as natural fibre for fishing gear materials. This research used the experimental method with used to test the breaking strength and elongation of the objects.Based on the histology, tissue of compiler at stems of bundung grass is a protective tissue (epidermis), the basic tissue (parenchyma), amplifier tissue (collenchyma and sclerenchyma) and carrier tissue (xylem and phloem). At the grass which has a length of 14 to 157 cm and a width ranging from 0.8 to 1.2 cm, where as for fine fibers produce reach 147 pieces with a diameter of 0,01 cm. Length of average of fine fibers produced at the grass was 58.39% length of grass. Bundung of fibres has the ability breaking load of 58,4 g, yarn 109 g and strand 853 g. Rope of fibres bundung grass has an average value of breaking strength and elongation of 1.8 kgf and 12.8 mm, while the rope from bundung grass stem with has an average value of breaking strength and elongation of 3.9 kgf and 20.1 mm. Bundung grass has potential used fishing gear material, but potential under of average other natural fibre after test.Keywords: Bundung grass, fishing gear material, histology, the breaking strength and elongation.